2019
DOI: 10.3390/jcm8081126
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil 5 mg Alone or in Combination with Tamsulosin 0.4 mg for the Management of Men with Lower Urinary Tract Symptoms and Erectile Dysfunction: Results of a Prospective Observational Trial

Abstract: Tadalafil 5 mg represents the standard for men with Erectile dysfunction (ED) and lower urinary tract symptoms (LUTS)/benign prostatic enlargement (BPE). We carried out an observational trial aiming to assess the efficacy and safety of Tadalafil compared with Tadalafil plus Tamsulosin. Seventy-five patients complaining of ED and LUTS were treated for 12-weeks with Tadalafil plus placebo (TAD+PLA-group) or with combination therapy tadalafil plus tamsulosin (TAD+TAM-group). Efficacy variables were: International… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…Interestingly, combined treatment with NaHS and tadalafil induced significantly higher levels of cGMP than controls. Previous data showed that the tadalafil augmented NO/cGMP pathway 1 . Also, a recent study has indicated that NaHS and l ‐cysteine increased cGMP accumulation and potentiated vasodilatory capacity of sildenafil in human CC and penile arteries 10 .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Interestingly, combined treatment with NaHS and tadalafil induced significantly higher levels of cGMP than controls. Previous data showed that the tadalafil augmented NO/cGMP pathway 1 . Also, a recent study has indicated that NaHS and l ‐cysteine increased cGMP accumulation and potentiated vasodilatory capacity of sildenafil in human CC and penile arteries 10 .…”
Section: Discussionmentioning
confidence: 95%
“…Lower urinary tract symptoms (LUTS) are often concurrent with benign prostatic hyperplasia (BPH) in older men 1 . The pharmacological management of BPH is primarily based on the use of 5‐alpha reductase inhibitors and alpha‐blockers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…No one experienced severe TEAEs. Headache, nasopharyngitis, back pain, and dizziness were the most frequent TEAEs [ 37 ••].…”
Section: Resultsmentioning
confidence: 99%